Impact of chronic pain on use-dependent plasticity: corticomotor excitability and motor representation in musicians with and without pain - Zamorano, Anna; De Martino, Enrico; Insausti-Delgado, Ainhoa; Vuust, Peter; Flor, Herta; Graven-Nielsen, Thomas (Brain topography, 2024)
Long-term musical training induces adaptive changes in the functional representation of the motor cortex. It is unknown if the maladaptive plasticity associated with chronic pain, frequently affecting trained musicians, may alter the use-dependent plasticity in the motor cortex. This study investigated the interaction between adaptive and maladaptive plasticity in the motor pathways, in particular how chronic pain influences long-term use-dependent plasticity. Using transcranial magnetic stimulation (TMS), corticospinal excitability was assessed by measuring the amplitude of the motor-evoked potential (MEP), area of the motor map, volume, and center of gravity of the first dorsal interosseous muscle in 19 pain-free musicians, 17 upper limb/neck pain chronic pain musicians, and 19 pain-free non-musicians as controls. Motor map volume and MEP amplitude were smaller for both pain-free and chronic pain musicians compared to pain-free controls (P < 0.011). No significant differences were found between musicians with and without chronic pain. These findings confirm that long-term musical training can lead to focalized and specialized functional organization of the primary motor cortex. Moreover, the adaptive use-dependent plasticity acquired through fine-motor skill acquisition is not significantly compromised by the maladaptive plasticity typically associated with chronic pain, highlighting the potential of long-term sensorimotor training to counteract the effects of chronic pain in the motor system.
Online veröffentlicht: 18. Januar 2024
Gesehen am 21.10.2024